Urgency of Legal Indigenous Communities' Position in Indonesian Constitutional System - Jaja Ahmad Jayus (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
Customary law community or Masyarakat Hukum Adat (MHA) in Indonesia has their own uniqueness and peculiarity in establishing relationships with the people and the surrounding environment. Along with the development of the era, the MHA experienced the complexity of the conflict of interest on the land tenure for business purposes or Hak Guna Usaha in the civil sphere, as well as conflicts within the scope of criminal law. The research analyzes legal indigenous communities’ position in the protection of normative law. The method used is normative or doctrinal law research that leans to a qualitative (non-numeric) based on secondary data which is analyzed qualitatively. Recognition and protection of the MHA in Indonesia is experiencing an uneasy phase. Since the independence of Indonesia the existence of MHA has only received adequate portions in the era of reformation with the Amendment of the Constitution 1945, enshrined in the Article 18b Paragraph 2 and Article 28i Paragraph 3, eight laws, and at least 22 (twenty two) regulations of the region either in the province, or regency/city, or decree of the local head of the area that recognizes the existence of the Communities. Nevertheless, the upper position of the MHA is felt not to provide maximum assurance and protection forthe Communities. The Indonesian House of Representatives (DPR) through the right of initiative encourages the draft law on MHA which currently becomes a national legislation program and become a priority in 2020 in providing recognition, protection, and empowerment of MHA. With the initiatives of the Bill, it is expected that the problems experienced by indigenous peoples are reduced drastically.